Sulfur dioxide (SO2) emission reduction and its spatial spillover effect in high-tech industries: based on panel data from 30 provinces in China - Lou, Lingyan; Li, Jian; Zhong, Shen (Environmental science and pollution research international, 2021)
Industrial sulfur dioxide (SO 2 ) has become an important source of environmental pollution in China, and the regional SO 2 emission reduction capacity is a comprehensive reflection of cleaner production capacity, environmental regulation, and economic development. It is obvious that high-tech industries play a crucial role in promoting the cleaner production capacity of the whole industry. Simultaneously, only considering the regional emission and the development of high-tech industry in isolation may deviate from actual economic characteristics. Therefore, by using the panel data of 30 provinces in China from 2005 to 2016, this paper adopts spatial autoregression model (SAR), spatial error model (SEM), and spatial Durbin model (SDM) to analyze the effect of the high-tech industry development on SO 2 emission reduction under the spatial adjacency matrix (W1), geographic distance matrix (W2), and economic distance matrix (W3). In addition, this paper selects three indicators, which is SO 2 removal rate, SO 2 emission, and SO 2 removal quantity, as explanatory variables, and R&D investment and number of enterprises in high-tech industry are selected to represent the industrial development level. The major conclusions are as follows: (1) The ability of SO 2 emission reduction in the local province is significantly affected by the surrounding provinces, showing the agglomeration characteristics of “high-high” or “low-low.” (2) The R&D investment of high-tech industry has a negative impact on SO 2 removal rate and SO 2 removal quantity, but a positive effect on the SO 2 emissions for the local province, and has a positive effect on the emission reduction of surrounding provinces. (3) The expansion of high-tech industry has significantly improved the SO 2 emission reduction capacity of the local province and its surrounding provinces. The robustness test supports the empirical conclusions of this paper. Finally, this paper puts forward some policy suggestions for government in environmental governance, such as “joint prevention and control” and the promotion of cleaner production. Graphical abstract